كيفية تطبيق الدوال المالية الاكتوارية لحساب القيم الحالية للمعاشات المستحقة عند التقاعد - عكروش محمد; دريباتي يسيرة; جلمودي دارين (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يتناول البحث كيفية تطبيق الدوال المالية الاكتوارية لحساب القيم الحالية للمعاشات المستحقة للموظف في حالة الوفاة أثناء الخدمة والمعاشات المستحقة لزوجة وأبناء صاحب المعاش بعد وفاة صاحب المعاش. حيث توصل البحث إلى نتائج أهمها وجود تزايد في قيم الدالة المعبرة عن نسبة الرواتب المتوقعة بين تمام العمر× والعمر(1+×) مع تزايد سنوات العمر والخدمة للمؤمن عليه. وجود تناقص في قيم الدالة المعبرة عن قيمة الدفعة المستحقة للأولاد الذكور من العمر ×hc وتستمر حتى العمر 21وهو الحد الأقصى الذي يتوقف بعده صرف المعاش للأبناء الذكور مع تزايد سنوات العمر والخدمة للمؤمن عليه، الأمر الذي يؤكد أهمية التأمين الاجتماعي في حياة المجتمع والحفاظ على حقوق العمال المؤمن عليهم، وحقوق عوائلهم في حال تحقق الخطر المؤمن منه. The research deals the method of applying the actuarial finance functions, which are necessary for counting the present values for deserved retirement salaries for the employee in the case of death during the service and the deserved salaries for the wife and sons of the salary owner after the death of the salary owner. so our previous study concluded a set of results abstracted as the following : existence of increase in the values of the function - which express about the ratio of expected salaries between complete age x and age (x+1) - by the growth in years of the age and the increase in the years of service of the insured , and existence of decrement in the values of the function -which express about the value of deserved payment for male sons from age x and continue until age 21 which is the maximum age after which spending pension is stopped- by the growth in years of the age and the increase in the years of service of the insured, the fact which emphasize the importance of the social insurance in the life of society and keeping the rights of the workers and the rights of their bread winners when the ensured risk is achieved.